Molecular movements of trehalose inside a single network enabling a rapidly-recoverable tough hydrogel. Issue 4 (2nd October 2022) - Huang, Xiaowen; Fu, Jimin; Tan, Huiyan; Miu, Yan; Xu, Mengda; Zhao, Qiuhua; Xie, Yujie; Sun, Shengtong; Yao, Haimin; Zhang, Lidong
ABSTRACT: It remains a challenge to achieve rapidly recoverable hydrogels by molecular hydrogen-bonding interaction because of its slow interaction kinetics. This work for the first time reports a trehalose (Tre)-based molecular movement mechanism inside a single network of polyacrylamide (PAM) that accelerates the kinetics of hydrogen-bonding interaction, and thereby endows the hydrogel with high toughness and rapid shape and mechanical recoverability. The resultant PAM@Tre hydrogel is capable of full shape recovery after 10, 000 loading/unloading cycles at a strain of 500%. Even after being stretched at a strain of 2500%, it can recover to its original shape within 10 seconds. Moreover, the molecular movement of trehalose also endows the PAM@Tre hydrogel with fracture energy and toughness as high as 9000 J m –2 and 1600 kJ m –3, respectively, leading to strong resistance to both static and dynamic piercing. The PAM@Tre hydrogel is thus believed to have enormous potentials in protection devices, bionic skin, soft actuator, and stretchable electronics. Graphical abstract: uf0001